2021
DOI: 10.5296/ije.v13i4.18965
|View full text |Cite
|
Sign up to set email alerts
|

EFL Teaching and Learning in the Rural Areas of Bangladesh: Addressing Obstacles to Teaching L2

Abstract: English as a language is an essential tool in the negotiation of power and relationship at the interpersonal, social and the global level as well. The importance of learning English has increased significantly as a useful communication tool in the age of globalization. In the existing scenario, English language learning and teaching in the rural areas of Bangladesh has become a prime concern. This study aims to present the current English language education policy, language learning and teaching obstacles pert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
0
0
Order By: Relevance
“…Teaching English as a foreign language in a rural education is challenging. Some previous studies have been revealed that rural school has lack of learning facilities and sources (Faisal & Ali, 2021;Izquierdo et al, 2021;Khan et al, 2020;Prabowo & Akmal, 2019;Putri, 2021;Saiful & Triyono, 2018). Due to the fact that most schools which are located in rural areas are not equipped with proper technology, including audio visual aids, it affected the learning techniques and strategies used by the teachers which mostly focus on grammar and mainly use L1 translation.…”
Section: The Implementation Of Project Based Learning In English Lang...mentioning
confidence: 99%
“…Teaching English as a foreign language in a rural education is challenging. Some previous studies have been revealed that rural school has lack of learning facilities and sources (Faisal & Ali, 2021;Izquierdo et al, 2021;Khan et al, 2020;Prabowo & Akmal, 2019;Putri, 2021;Saiful & Triyono, 2018). Due to the fact that most schools which are located in rural areas are not equipped with proper technology, including audio visual aids, it affected the learning techniques and strategies used by the teachers which mostly focus on grammar and mainly use L1 translation.…”
Section: The Implementation Of Project Based Learning In English Lang...mentioning
confidence: 99%